Social media use in international marketing: Impact on brand and firm performance - Marzanna K. Witek-Hajduk; Piotr Zaborek (International Journal of Management and Economics, 2022)
This research investigates the influence of brand and customer orientations on social media (SM) marketing engagement and how applications of SM in international marketing affect brand and firm performance in foreign markets. The study relies on a survey of a representative sample of 245 medium and large companies using SM in international branding. Performance metrics include an index of brand performance (BP) in a foreign market and return on assets (ROA). Structural equation modeling analysis reveals the overall effect of SM use in international branding as positive, with brand-image creation and market research being significant contributors to brand and firm performance in a foreign market. SM effectiveness is negatively moderated by foreign partner involvement and centralization degree. Firms co-owned by foreign entities turn out to be more successful than their Polish-only counterparts. Of the two antecedents of SM international marketing engagement, customer orientation is significant for all firms, while brand orientation is meaningful only for those with foreign capital.
Keywords: F23; M31; 650; brand orientation; customer orientation; international branding; performance; social media marketing